Efficacy of indocyanine green fluorescence imaging-guided lymphadenectomy in radical gastrectomy for gastric cancer: A systematic review and meta-analysis - Dong, Bo; Zhang, Anyuan; Zhang, Yuqiang; Ye, Wei; Liao, Lan; Li, Zonglin (Frontiers in Oncology, 2022)
Background: Indocyanine green (ICG) imaging-guided lymphadenectomy has been introduced in gastric cancer (GC) surgery and its clinical value remains controversial. The aim of this study is to evaluate the efficacy of ICG fluorescence imaging-guided lymphadenectomy in radical gastrectomy for GC. Methods: Studies comparing lymphadenectomy in radical gastrectomy between use and non-use of ICG fluorescence imaging up to July 2022 were systematacially searched from PubMed, Web of Science, Embase and Cochrane Library. A pooled analysis was performed for the available data regarding the baseline features, the number of retrieved lymph nodes (LNs), the number of metastatic LNs and surgical outcomes as well as oncological outcomes. RevMan 5.3 software was used to perform the statistical analysis. Quality evaluation and publication bias were also conducted. Results: 17 studies with a total of 2274 patients (1186 in the ICG group and 1088 in the control group) undergoing radical gastrectomy and lymphadenectomy were included. In the pooled analysis, the baseline features were basically comparable. However, the number of retrieved LNs in the ICG group was significantly more than that in the control group (MD = 7.41, 95% CI = 5.44 to 9.37, P < 0.00001). No significant difference was found between the ICG and control groups in terms of metastatic LNs (MD = -0.05, 95% CI = -0.25 to 0.16, P = 0.65). In addition, the use of ICG could reduce intraoperative blood loss (MD = -17.96, 95% CI = -27.89 to -8.04, P = 0.0004) without increasing operative time (P = 0.14) and overall complications (P = 0.10). In terms of oncological outcomes, the use of ICG could reduce the overall recurrence rate (OR = 0.50; 95% CI 0.28-0.89; P = 0.02) but could not increase the 2-year overall survival rate (OR = 1.25; 95% CI 0.72-2.18; P = 0.43). Conclusions: ICG imaging-guided lymphadenectomy is valuable for complete LNs dissection in radical gastrectomy for GC. However, more high-quality randomized controlled trials are needed to confirm this benefit.